Prevalence and ultrasonographic patterns of gynecological emergencies in southeastern Nigeria - Emmanuel Odumeru; Xavier Akimuhana; Eric Kirezi; Costelia Njoku (Academia Medicine, 2025)
Background: There is an increasing prevalence of gynecological emergencies (GEs) associated with acute pelvic pain (APP) globally, and it is of concern locally with anthropometric factors. Sonography plays a pivotal role in the assessment of these emergencies. Objective: This study aimed to assess the prevalence of GEs, their relationship with anthropometric characteristics, and the sonographic description of the abnormalities. Materials and methods: An analytical cross-sectional study design was adopted using a convenience purposive sampling method on 300 patients between 20 and 49 years diagnosed clinically for GE and confirmed with an ultrasound machine. Consent and confidentiality were considered. Descriptive statistics such as mean, standard deviation, and percentage were used for the prevalence and anthropometric data; a Standard Error of Mean (SEM) at a 95% Confidence Interval (CI) and Pearson’s Correlation established the relationship, and the p value was set at <0.05. Result: Tubovarian abscess (TOA) was recorded as highest (67) (22.33%) and most prevalent in the age group of 20–24 years (18) (26.9%). A strong negative correlation and significance were recorded between TOA and Age, R= −0.964, p = 0.002, respectively, but not significant with height (p = 0.49), weight (p = 0.71), and body surface area (BSA) (p = 0.37) amongst others. Conclusion: Women within the age group of 35–45 years are more prone to develop various forms of GE; younger women, particularly those aged 20–24 years, more prevalently develop Tubo-Ovarian Abscess (TOA), a specific type of GE, in the locality, probably due to their lifestyle, avoidable infection, and frequent uterine instrumentation. Further studies are required to evaluate these causative factors of GE using sonographic imaging.